Investigation of candidate genes reveals significant statistical epistasis between DISC1 and TPH2 in Bulgarian affective disorder patients. Issue 6 (2nd November 2017) - Ivanova-Stoevska, Mina; Penchev, Mladen; Stoyanova, Vessela; Vladimirova, Rossitza; Milanova, Vihra; Kremensky, Ivo; Mitev, Vanio; Kaneva, Radka
ABSTRACT: The aim of the present study was to search for joint influence of variants in affective disorder (AD) candidate genes by investigating statistical epistasis. Overall 24 single nucleotide polymorphisms (SNPs) in 9 AD candidate genes were analysed in 304 AD cases (270 bipolar disorder (BD) type I; 29 BD type II; 5 schizoaffective disorder bipolar type, 110 major depressive disorder) and 205 healthy prescreened controls. The results demonstrated statistical epistasis between variants in DISC1, TPH2, CRH, CLOCK, BDNF, ANK3 and SLC6A4 . Multiple interactions involving TPH2, both protective and increasing the AD risk, were detected. Protective epistasis surviving Bonferroni correction was observed between DISC1 and TPH2, justifying further analysis, given their role in neurogenesis and synaptic plasticity and serotonin biosynthesis.